Timing and Frequency Matter: Same Race/Ethnicity Teacher and Student Achievement by School Level and Classroom Organization. Issue 5 (July 2023) - Hwang, NaYoung; Graff, Patrick; Berends, Mark
Existing research examines whether studying with teachers of the same race/ethnicity affects student achievement, but little is known about whether those effects vary by timing and frequency. We use 7 years of administrative data from third through eighth graders in Indiana to estimate the heterogenous links between same race/ethnicity teachers and achievement by school level (i.e., elementary vs. middle schools) and self-contained classroom (i.e., self-contained vs. departmentalized classrooms). We find that the positive links between same race/ethnicity teachers and improved achievement are stronger for elementary school students and students in self-contained classrooms, particularly for Black students. Our findings highlight the importance of timing and frequent exposure to same race/ethnicity teachers in academic trajectories.